Pengaruh Variasi Produk dan Kreativitas Iklan terhadap Keputusan Pembelian Konsumen pada Produk Scarlett Whitening di Kota Palembang - Puteri, Fatimah Eka; Andriana, Isni; Yunita, Dessy; Mavilinda, Hera Febria (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of of variation of products and advertising creativity on consumer purchase decisions for Scarlett Whitening products in Palembang City. The type of research used is quantitative descriptive research. Data collection methods in this study using a questionnaire, samples taken as many as 100 people using the purvosive salmpling method. The analysis technique used is multiple linear regression analysis. Based on the results of the study it can be concluded that variation of products and advertising crearivity has a significant effect on on consumer purchase decisions for Scarlett Whitening Products in Palembang City. Keywords: Variation of Products, Advertising Crearivity, Consumer Purchase Decisions